Cochlear implant in immune mediated inner ear diseases: Impedance variations and clinical outcomes. (4th March 2022) - Atturo, Francesca; Portanova, Ginevra; Russo, Francesca Yoshie; Seta, Daniele De; Mariani, Laura; Borel, Stephanie; Greco, Antonio; Mosnier, Isabelle; Mancini, Patrizia
Abstract : OBJECTIVE: Immune-mediated inner ear disease (IMIED) might cause severe/profound hearing loss and these patients are considered ideal candidates to cochlear implant (CI) surgery. The aim of the study was to evaluate impedance changes over time. METHOD: The Study Group (SG) was composed of CI IMIED patients (31 ears) and a Control Group (CG) of CI patients with hearing loss not related to their immune system (31 ears). Audiological performance and impedance values were measured and compared amongst groups at 3, 6, 12 and 18 months following the fitting sessions. RESULTS: Speech perception was significantly better for SG in word and sentence recognition in quiet. Impedance values were, on average, significantly higher for apical and middle electrode segments in SG compared to CG at the 3- month follow-up and were maintained over time. Additionally, a subset of SG patients (active patients) experienced significantly greater impedance fluctuation corresponding to clinical symptom reactivation. CONCLUSION: IMIED patients achieve good audiological performance. However, the relapsing inflammation could change the inner ear environment, causing impedance fluctuations and, consequently, more frequent CI fittings. Additionally, impedance evaluation could be utilized as an early warning sign of IMIED recurrence and as an aid to therapeutic decision-making.